Where leaders learn: constructions of leadership and leadership development at Rhodes University - Andrews, Rushda Ruth (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
This thesis explores the Where Leaders Learn slogan of Rhodes University. It does this by means of an analysis of discourses constructing leadership and leadership development within the institutional context. The discourse analysis was made possible as a result of interviews with a range of people involved in leadership and leadership development at the University. The analysis revealed that leadership development is constructed as taking place within a highly structured system that enables instructional and managerial leadership but constrains transformational leadership. The discourses that give meaning and understanding to the construct of leadership draw heavily on position within a hierarchy. The discourse of functional efficiency is enabled through practices related to reward, recognition, succession planning and mentorship which all serve to replicate the existing leadership structures creating more of the same and in essence stifling the potential for emancipatory leadership. The analysis also shows that a discourse of collegiality serves to create a false sense of a common understanding of leadership in the light of evidence of uncertainty and contestation around the meaning of the slogan Where Leaders Learn and, by association, the very construct of leadership. The discursive process of understanding leadership and developing an institutional theory for the purposes of infusing this into a curriculum poses many challenges. Barriers to new ways of thinking reside within the researchers' ontological and epistemological commitments. This amplifies the need for a more reflective ontology towards leadership and its consequences, especially so in a multidisciplinary environment such as Rhodes University.
Keywords: Leadership -- Education (Higher) -- South Africa -- Grahamstown; Leadership -- Research -- South Africa -- Grahamstown; Development leadership -- Education (Higher) -- South Africa -- Grahamstown; Rhodes University -- Management